Teaching English for specific purposes: novice teachers’ perspectives - Vial, Ana Paula Seixas; Acorinti, Wesley Henrique; Sarmento, Simone (The ESPecialist, 2024)
Considering the need to engage with English at the university level (Hyland, 2009), this study investigates the perspectives of novice teachers regarding the teaching of English for Academic Purposes (EAP). The results of this qualitative (Mason, 2002) and interpretive (Erickson, 1990) research, based on semi-structured interviews, reveal that these teachers perceive EAP as a mode of communication centered around skills for academic participation. On one hand, teachers point out that textbooks do not fully meet the needs of an EAP class. On the other hand, they acknowledge the relevance of these materials for curriculum development. Additionally, they recognize the importance of partnering with students to address disciplinary differences. Furthermore, they explicitly discuss the challenge of teaching EAP to students with basic proficiency levels but find strategies to address it. This research has implications for teacher training in EAP.